Penambatan Molekuler dan Simulasi Dinamika Molekuler Senyawa Dari Genus Nigella Terhadap Penghambatan Aktivitas Enzim Protease HIV-1: Molecular Docking and Molecular Dynamics Simulation of Compounds from Nigella Genus on Protease HIV-1 Enzyme Inhibitors - Zubair, Muhammad Sulaiman; Maulana, Saipul; Mukaddas, Alwiyah (Universitas Tadulako, 2020)
Nigella plant genus has potential as anti-HIV. One species of Nigella, Nigella sativa has been reported to have HIV-1 protease enzyme inhibitory activity. This research aims to determine the compounds of the Nigella genus that have activity as HIV-1 protease enzyme inhibitory activity through molecular docking method by Autodock Vina and to compare interaction stability through molecular dynamics simulations by AMBER. The metabolite of the Nigella genus was obtained from the KnapSack website, and enzyme model was obtained from the Protein Data Bank (3NU3). The results of molecular docking found the lowest affinity energy of Nigella compound is Nigellidine 4-O-sulfite (-13.4 kcal/mol). Meanwhile, the affinity energy of the ligand native (Amprenavir) was -12.1 kcal/mol. The lowest affinity energy of Nigellidine 4-O-sulfite might be predicted to have potency as an HIV-1 Protease inhibitor. Molecular dynamics simulation showed Root Mean Square Fluctuation (RMSF) value of Nigellidine 4-O-sulfite with the amino acid active site is 0.4064 Å for ASP:25 and 0.5667 Å for ASP: 125. Whereas RMSF ligand native with the amino acid active site, ASP: 25 is 0.3647 Å and ASP: 125 is 0.3639 Å. The higher RMSF value of Nigellidine 4-O-sulfite describes the lower interaction stability than the ligand native.